Solanum xanthocarpum Plant as a Potential Low Cost Adsorbent for the Removal of Methylene Blue from Aqueous Solutions. (5th October 2018) - Zaman, Muhammad Iqbal; Khan, Siffat Uullah; Shahnaz, Aysha; Niaz, Abdul; Khan, Sadullah; Muhammad, Nawshad; Khan, Matiullah; Shah, Khizar Hussain
Abstract : This study reports the removal of methylene blue (MB) from aqueous solution by powdered fruit of Solanum xanthocarpum plant which is important in terms of its applicability in the decontamination of water through an environmental friendly and low cost adsorbent. The biosorbent has a BET surface area of 3.09 m 2 /g while FE‐SEM and FTIR analyses show that it is a porous material having OH, CH, CO, and SO3 ‐H surface groups. The sorption equilibrium experiments show that sorption of MB increases with increasing pH, temperature, initial concentration, and sorbent dosage. The sorption equilibrium data fits well to Langmuir adsorption isotherm. The values of the isosteric heat of sorption (ΔH), being positive are consistent with the endothermic nature of the sorption process. Sorption kinetics experiments of MB onto the biosorbent show that equilibrium is established in about 180 minutes at both the pH values of 6 and 5.2 and that the data give best fit to pseudo‐second order kinetics model. The maximum adsorption capacity of the biosorbent for MB is about 0.05067 mmol/g. Sorption data along with the spectroscopic analyses suggests that MB is removed from the aqueous solution by the sorbent mostly through ion exchange, adsorption, diffusion, and surface precipitation. © 2018 American Institute of Chemical Engineers Environ Prog, 38: S166–S175, 2019